Book Review of “The Practice of Collaborative Counseling and Psychotherapy: Developing Skills in Culturally Mindful Helping” - Audet, Cristelle (Canadian Journal of Counselling and Psychotherapy, 2014)
This book provides a clear framework for developing a collaborative counselling approach with clients. Dr. Paré espouses an alternative view of counselling as a conversational practice that considers power, meaning, and social justice when working with rather than working on clients. He delivers tools for practitioners to mindfully step away from deficit-based views of clients toward client agency. This accessible text focuses on building a foundation of collaboration with clients, explores the practice of collaborative meaning making, and provides empowering practices for assessing client concerns and promoting change. Students and practitioners alike will appreciate this guiding compass for the complex counselling conversations that lie ahead.